INCIDENCIA DEL POLVO PROTEICO DE Dosidicus gigas “POTA” EN LAS CARACTERÍSTICAS FISICOQUÍMICAS EN EL PERÍODO DE INCUBACIÓN DEL YOGUR - Córdova, Javier S. (2017)
The purpose of the research was to evaluate the influence of protein powder Dosidicus gigas “pota” (PPP) on the physicochemical characteristics during incubation period of yogurt. Milks previously standardized with PPP 1 (YM1), 3 (m2), 5 (YM3), 7 (YM4) and 10% w/v (YM5), plus one control (YM6), were treated, inoculated with ferment dairy 0,002% (w/v) each treatment; finally incubated for six hours at 42°C. During the milk fermentation, every hour were measured the pH, acidity and viscosity. The PPP had a favorable impact on the physicochemical characteristics of yogurt. At the end of the incubation period it was observed that the percentage of acidity reached 1,02 in the treatment YM5, causing decrease in pH to 4,28; the viscosity was higher (58550cP) in treatment YM5. Finally, after three hours of incubation, reached the characteristics required for a good yogurt.